Monitoring Biomarkers After Pediatric Heart Surgery: A New Paradigm on the Horizon - (:unkn) unknown (WILEY-BLACKWELL, 2013)
Until recently, risk scoring systems for adult patients consisted of only clinical criteria. Currently, we are experiencing an abundant surge of literature integrating a wide range of biomarker arrays to clinical criteria in assessing the risk in an adult. In fact, novel risk scoring systems such as Reynolds criteria have emerged by combining the validated biomarkers to the traditional risk factors. Novel biomarkers potentially improve clinical management of cardiovascular disease, but there are gaps in understanding their role during childhood. The reason might be related to relatively lower prevalence of cardiovascular disease in children compared to the adult population. One exceptional group is the children with congenital heart disease. Recent studies indicate that novel biomarkers can alert the clinician in a timely manner about neurological and myocardial injury and their inflammatory consequences. Current technologies enable us to measure several biomarkers using only a few microliters of plasma. The preliminary studies show that novel biomarkers in addition to the traditionally studied biomarkers can help the clinician to identify children at high risk following pediatric heart surgery. Future studies are needed to confirm the role of biomarkers in monitoring children after cardiopulmonary bypass.
Keywords: Pediatric heart surgery; Biomarkers; Cardiopulmonary bypass; Outcomes; Congenital heart disease; FIBRILLARY ACIDIC PROTEIN; ACUTE CORONARY SYNDROMES; TRAUMATIC BRAIN-INJURY; CARDIOPULMONARY BYPASS; CARDIAC-SURGERY; PLASMA-PROTEIN; SERUM; MARKERS; DISEASE; FEASIBILITY